2022
DOI: 10.1101/2022.04.08.487694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The PAICE Suite Reveals Circadian Post-Transcriptional Timing of Non-Coding RNAs and Spliceosome Components in Mus musculus Macrophages

Abstract: Circadian rhythms broadly regulate physiological functions by tuning oscillations in the levels of mRNAs and proteins to the 24-hour day/night cycle. Globally assessing which mRNAs and proteins are timed by the clock necessitates accurate recognition of oscillations in RNA and protein data, particularly in large omics data sets. Tools that employ fixed-amplitude models have previously been used to positive effect. However, the recognition of amplitude-change in circadian oscillations required a new generation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The importance of minor intron splicing is evident by the fact that minor-intron containing genes are highly conserved and thirteen diseases have been linked to mutations in minor splicing components, including the neurodegenerative diseases, amyotrophic lateral sclerosis, and spinal muscular atrophy (52,54,55). A study by Buel and colleagues found oscillations in many components of the major spliceosome pathway mirror that of the clock and bmal1 transcripts (56), indicating that the major spliceosomal pathway is at least partly regulated by the circadian clock. This is interesting in relation to the minor spliceosome too, given the overlap in these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of minor intron splicing is evident by the fact that minor-intron containing genes are highly conserved and thirteen diseases have been linked to mutations in minor splicing components, including the neurodegenerative diseases, amyotrophic lateral sclerosis, and spinal muscular atrophy (52,54,55). A study by Buel and colleagues found oscillations in many components of the major spliceosome pathway mirror that of the clock and bmal1 transcripts (56), indicating that the major spliceosomal pathway is at least partly regulated by the circadian clock. This is interesting in relation to the minor spliceosome too, given the overlap in these pathways.…”
Section: Discussionmentioning
confidence: 99%